The Influence Of Organizational Climate, Commitment And Job Satisfaction On Job Performance At Bengkulu Province Environment And Forestry Service - Tio Wichaksono Sagutro; Anzori Anzori; Karona Cahya Susena (Utan Kayu Publishing, 2024)
Organizational climate, commitment, and joh sarisfaction on joh performance are a person's awareness and willingness to obey all company regulations and applicable social norms. This view explams a person's willingness to ohey the mules that apply without coercion. The purpose of this study was to analyze the organizational climate, commitment, and joh safisfaction on job performance al Bengkulu Province Environmert and Forestry Service. The sampling method used is Simple Random Sampling with a sample size of 65 people. The analysis method in this research is qualitative analysis. Of the four research indicators, an average value of 264.75 was obtatned in the interval 222-273 with the critera agreeing. meaning that overall, the ASN (employee) at Bengkulu Province Environment and Forestry Service has enforced the orgamzational climate, commitment, and job satisfaction on job performance well. The organizational climate indicator obtained the highest value, namely a value of 275, which is in the interval 274-325 with the criteria strongly agree, meaning that ASN at Bengkulu Province Knwironment and Korestry Service has very high work discipline assessed from the organizational climate indicator. The indicator with the lowest value is work performance with a value of 257, which is in the interval 222-273 with agreed criteria.